MODEL INTERVENSI PSIKO-EKONOMI: INTEGRASI MANAJEMEN STRES DAN DIGITAL ENTREPRENEURSHIP MELALUI WHATSAPP BUSINESS BAGI IBU RUMAH TANGGA - Novi Lailiyul Wafiroh; Nanik Wahyuni; Lutfi Ardhani (Jurnal AbdiMas Nusa Mandiri, 2026)
Stress among housewives is frequently triggered by domestic economic pressures, leading to physical exhaustion and emotional dysregulation. Conventional interventions typically separate psychological support from economic empowerment, preventing the simultaneous resolution of root causes. The novelty of this community service program lies in the implementation of an Integrated Psycho-Economic Intervention Model, which incorporates stress management psychoeducation as a cognitive pre-condition phase prior to technical digital marketing training via WhatsApp Business. The method employed is community development needs-based approach, involving 51 housewives in RW 11 Villa Bukit Tidar, Malang. Situational analysis reveals that stress is driven by economic factors, household chores, and health concerns, manifesting primarily as physical fatigue (score 2.92) and emotional dysregulation (score 2.73). Nevertheless, respondents demonstrate a tendency toward adaptive coping, particularly relying on religious/spiritual activities (score 4.69) and positive thinking (score 4.25). The results indicate that stress management effectively reduces partners' emotional tension, subsequently enhancing their readiness to adopt professional WhatsApp Business features for local entrepreneurship. This integration proves that mental stability serves as a foundation for digital productivity, while economic access acts as a long-term solution to reduce domestic stress determinants. This program offers a new framework for community empowerment that synergizes mental health and sustainable economic resilience.